“Vaai Ganam” - a screening program for early detection of oral potentially malignant disorders and oral cancer among truck drivers in Chennai – a cross-sectional survey - Madan Kumar, Parangimalai Diwakar; Loganathan, Kavitha; Kannan, Ranganathan; Roa, Uma Devi Mohan Das; Bhagiyalakshmi, Aswath Narayanan Mani (International Journal of Occupational Safety and Health, 2024)
Introduction: Truck drivers, though forming an integral part of a vital trade link for the Indian population, lack basic life insurance and health care benefits offered by other organized sectors in Indian Industries. This paper aims to present the initial findings of the “VaaiGanam” program which proposes to identify tobacco use and the prevalence of Oral potentially malignant disorders (OPMDs) among truck drivers who are stationed or passing via Chennai and provide cessation services by behavioral therapy. Methods: This cross-sectional study was conducted by a dental screening team who were involved in data collection and screening of the 747 truck drivers who fulfilled the inclusion and exclusion criteria between Jan to Oct 2022. After data collection, oral examinations were done and suspicious lesions were sought for expert opinion. A standard punch biopsy was taken from those lesions requiring confirmation. Results: Among the 747 subjects who participated in this program, 704 (94.2%) were current users of various tobacco products, with 235 (31.4%) preferring smoking and the rest 469(62.8%) using smokeless tobacco products. Oral mucosal lesions were recorded in 49 (6.5%) of the study population, mostly among tobacco users. Punch/incisional biopsies were taken among 17 of the 49 subjects and oral dysplasia was histopathologically confirmed in 9 (mild epithelial dysplasia = 5; moderate epithelial dysplasia = 4) subjects. Conclusion: Truck drivers with tobacco and substance abuse are at high risk of developing oral cancer and hence this study emphasizes the importance of periodic oral cancer screening programs for this vulnerable population to identify potentially malignant oral lesions at an early stage.